a^2(a^2-4c^2)-b^2(a^2-4c^2) 这步之后怎麼得到 (a^2-4c^2)(a^2-b^2)...

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/21 11:51:35
a^2(a^2-4c^2)-b^2(a^2-4c^2) 这步之后怎麼得到 (a^2-4c^2)(a^2-b^2)...

a^2(a^2-4c^2)-b^2(a^2-4c^2) 这步之后怎麼得到 (a^2-4c^2)(a^2-b^2)...
a^2(a^2-4c^2)-b^2(a^2-4c^2) 这步之后怎麼得到 (a^2-4c^2)(a^2-b^2)
...

a^2(a^2-4c^2)-b^2(a^2-4c^2) 这步之后怎麼得到 (a^2-4c^2)(a^2-b^2)...
a^2(a^2-4c^2)-b^2(a^2-4c^2)
提取公因式(a^2-4c^2)
a^2(a^2-4c^2)-b^2(a^2-4c^2)
= (a^2-4c^2)(a^2-b^2)

大哥,提取公因式。。。。(a^2-4c^2),剩下的不就是(a^2-b^2)了么。。

原式=a^4-4a^2c^2-a^2b^2+4b^2c^2=a^2(a^2-b^2)+4c^2(b^2-a^2)=所求 太难输入了呵呵